SARS-CoV-2 RNA Persistence in Naso-Pharyngeal Swabs - Maria Luisa Danzetta; Laura Amato; Francesca Cito; Alessandra Di Giuseppe; Daniela Morelli; Giovanni Savini; Maria Teresa Mercante; Alessio Lorusso; Ottavio Portanti; Ilaria Puglia; Federica Monaco; Claudia Casaccia; et al. (Microorganisms, 2020)
Since February 2020, Italy has been seriously affected by the SARS-CoV-2 pandemic. To support the National Health Care system, naso-pharyngeal/oropharyngeal swabs collected from suspected cases of Teramo province, Abruzzo region, are tested at Istituto Zooprofilattico Sperimentale dell’Abruzzo e del Molise G. Caporale, for the presence of SARS-CoV-2 RNA. Out of 12,446 tested individuals, 605 returned positive results at least once, with prevalence significantly higher in men. A reduction of the level of viral RNA in the first swab per each positive patient collected over time was also observed. Moreover, 81 patients had at least one positive sample and two final negative tests: positivity in swabs lasted from 14 to 63 days, with a median value of 30 days. This shows the potential for the virus to coexist with patients for a long time, although we highlighted intermittent positivity in several cases. The evolution of the SARS-CoV-2 epidemiological situation and knowledge on viral shedding should be closely monitored, to interpret the findings correctly and adjust accordingly the surveillance activities.